Influence of absolute versus relative L-arginine dosage on 1 km and 16.1 km time trial performance in trained cyclists - Hurst, H. T.; Sinclair, J.; Beenham, M. (Journal of Science and Cycling, 2014)
This investigation aimed to determine the effects of L-arginine supplementation on cycling time trial (TT) performance. Eight trained male cyclists performed 1 and 16.1km time trials on three occasions, control (CON), absolute (ABS) and relative (REL) loading. Participants consumed 500ml of water with either 6g (ABS), 0.15 g/kg body mass (REL) of L-arginine or water (CON) 90min prior to testing. Time to completion, mean power output (Wmean) and post-exercise lactate (La) were recorded for each TT. Time to completion decreased non-significantly for 1 and 16.1km TT`s during ABS and REL trials compared to CON. Wmean was significantly different between CON and REL during 16.1 km TT (196.19 ± 32.40W and 215.81 ± 31.56W). Blood lactates was significantly different between CON and ABS for the 1 km TT (p = 0.04) (13.59 ± 1.21 mmol/l and 12.38 ± 0.70 mmol/l, respectively) and between CON and ABS (p = 0.04) (9.11 ± 2.91mmol/l and 7.64 ± 3.01mmol/l, respectively) and CON and REL (9.11 ± 2.91 mmol/l and 7.15 ± 2.96 mmol/l, respectively) for 16.1km TT. These results indicate L-arginine supplementation does not significantly improve cycling TT performance, though there was a trend towards reduced time to completion and increased mean power output, and that relative doses appear more effective than absolute doses.